BIBLIOMETRIC ANALYSIS OF PLANT TISSUE CULTURE RESEARCH IN SUPPORTING THE BIOECONOMY AND SUSTAINABLE AGRICULTURE - Rut Normasari; Shapely Ambalao (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Plant tissue culture is a foundational plant biotechnology approach with applications in micropropagation, clean planting material production, germplasm conservation, and biotechnology-based agribusiness. This article reports a bibliometric analysis of plant tissue culture and micropropagation literature connected with economic, commercialization, and bioeconomy-related terms. The Scopus search identified 1,048 records. Sequential eligibility screening excluded 414 non-article document types, 58 non-English records, and 23 non-journal source records, resulting in 553 English-language journal articles for analysis. The corpus covered 1973–2026, with publication output peaking at 71 documents in 2025; the 2026 count of 25 was partial at the time of export. Plant Disease was the leading source with 33 documents. China (119), India (77), the United States (57), Brazil (42), and Iran (22) were the most productive countries. Garibaldi, A. and Gullino, M. L. each contributed five documents, while the National Natural Science Foundation of China supported 38 documents. Author keyword analysis confirmed that micropropagation, plant tissue culture, tissue culture, medicinal plant, somatic embryogenesis, plant growth regulators, and somaclonal variation were the dominant concepts. The findings show growing research activity but also demonstrate that the broad Scopus query retrieves a field-level corpus extending beyond narrowly defined tissue-culture and bioeconomy studies. However, explicit bioeconomy, green economy, and agribusiness terminology remained rare, indicating that the economic contribution of plant tissue culture is more often framed through commercialization, economic value, propagation efficiency, and crop-specific applications than through bioeconomy policy language. The study suggests that future research should integrate plant tissue culture protocols with cost analysis, value-chain studies, certification systems, nursery economics, and farmer adoption research. Keywords: plant tissue culture; micropropagation; bibliometric analysis; bioeconomy; commercialization; sustainable agriculture; Scopus   Abstrak: Kultur jaringan tanaman merupakan pendekatan bioteknologi tanaman yang fundamental dengan penerapan dalam mikropropagasi, produksi bahan tanam bersih, konservasi plasma nutfah, dan agribisnis berbasis bioteknologi. Artikel ini melaporkan analisis bibliometrik terhadap literatur kultur jaringan tanaman dan mikropropagasi yang berkaitan dengan istilah-istilah ekonomi, komersialisasi, dan bioekonomi. Pencarian di Scopus mengidentifikasi 1.048 rekaman. Penyaringan kelayakan secara bertahap mengecualikan 414 dokumen yang bukan artikel, 58 rekaman yang bukan berbahasa Inggris, dan 23 rekaman yang bukan berasal dari jurnal, sehingga menghasilkan 553 artikel jurnal berbahasa Inggris untuk dianalisis. Korpus data mencakup rentang waktu 1973–2026, dengan jumlah publikasi mencapai puncaknya sebanyak 71 dokumen pada tahun 2025; jumlah 25 dokumen pada tahun 2026 merupakan data parsial pada saat ekspor data dilakukan. *Plant Disease* merupakan sumber publikasi utama dengan 33 dokumen. Tiongkok (119), India (77), Amerika Serikat (57), Brasil (42), dan Iran (22) adalah negara-negara paling produktif. Garibaldi, A. dan Gullino, M. L. masing-masing berkontribusi lima dokumen, sementara *National Natural Science Foundation of China* mendukung 38 dokumen. Analisis kata kunci penulis mengonfirmasi bahwa mikropropagasi, kultur jaringan tanaman, kultur jaringan, tanaman obat, embriogenesis somatik, zat pengatur tumbuh tanaman, dan variasi somaklonal merupakan konsep-konsep yang dominan. Temuan ini menunjukkan peningkatan aktivitas penelitian, namun juga memperlihatkan bahwa kueri Scopus yang luas menghasilkan korpus tingkat bidang yang melampaui batasan studi kultur jaringan dan bioekonomi yang sempit. Akan tetapi, penggunaan istilah eksplisit terkait bioekonomi, ekonomi hijau, dan agribisnis masih jarang ditemukan; hal ini mengindikasikan bahwa kontribusi ekonomi kultur jaringan tanaman lebih sering dibahas melalui aspek komersialisasi, nilai ekonomi, efisiensi propagasi, dan penerapan spesifik tanaman dibandingkan melalui bahasa kebijakan bioekonomi. Studi ini menyarankan agar penelitian di masa mendatang mengintegrasikan protokol kultur jaringan tanaman dengan analisis biaya, studi rantai nilai, sistem sertifikasi, ekonomi pembibitan, dan penelitian mengenai adopsi oleh petani. Kata kunci: kultur jaringan tanaman; mikropropagasi; analisis bibliometrik; bioekonomi; komersialisasi; pertanian berkelanjutan; Scopus